The Implementation Entrepreneurship Orientation, Market Orientation and Business Performance Model for Food Category of Micro and Small Entreprises - Octavia, Ade; Dewi, Erwita; Sriayudha, Yayuk (Dinasti International Journal of Digital Business Management, 2023)
This Study aim to analyze how implementation model of entrepreneurial orientation, market orientation and business performance on Micro and Small Entreorises for food category in City Jambi. Study this is qualitative research. The approach used in this research is a case study of the research object, Micro and Small Enterprises in term of food and beverage entreprises. The determination of informants in this research, it was carried out using a purposive sampling technique where selection was carried out deliberately based on predetermined criteria and set based on objectives study. Informant study This is: Manager/owner Business Micro and Small category Food in Jambi. The research results show that food business owners have an entrepreneurial orientation and understand market desires (market orientation). MSEs understand that the more market-oriented and entrepreneurial they are, the better their business performance will be. The use of technology in the form of social media as a means of promotion has been carried out, but the courage to take risks is still low.